Mechanical Function of the Nucleus Pulposus of the Intervertebral Disc Under High Rates of Loading. Issue 15 (1st August 2019) - Newell, Nicolas; Carpanen, Diagarajen; Evans, John H.; Pearcy, Mark J.; Masouros, Spyros D.
Abstract : Study Design: Bovine motion segments were used to investigate the high-rate compression response of intervertebral discs (IVD) before and after depressurising the nucleus pulposus (NP) by drilling a hole through the cranial endplate into it. Objective: To investigate the effect of depressurising the NP on the force–displacement response, and the energy absorption in IVDs when compressed at high strain rates. Summary of Background Data: The mechanical function of the gelatinous NP located in the center of the IVDs of the spine is unclear. Removal of the NP has been shown to affect the direction of bulge of the inner anulus fibrosus (AF), but at low loading rates removal of the NP pressure does not affect the IVD's stiffness. During sports or injurious events, IVDs are commonly exposed to high loading rates, however, no studies have investigated the mechanical function of the NP at these rates. Methods: Eight bovine motion segments were used to quantify the change in pressure caused by a hole drilled through the cranial endplate into the NP, and eight segments were used to investigate the high-rate response before and after a hole was drilled into the NP. Results: The hole caused a 28.5% drop in the NP pressure. No statistically significant difference was seen in peak force, peak displacement, or energy-absorption of the intact, and depressurized NP groups under impact loading. The IVDs absorbed 72% of the input energy, and there was no rate dependency in the percentage energy absorbed. Conclusion: These results demonstrate that the NP pressure does not affect the transfer of load through, or energy absorbed by, the IVD at high loading rates and the AF, rather than the NP, may play the most important role in transferring load, and absorbing energy at these rates. This should be considered when attempting surgically to restore IVD function. Level of Evidence: N/A Abstract : High-rate compression behavior of intervertebral discs was investigated before and after decompressing the nucleus pulposus by drilling a hole into it. This did not affect load transfer or energy absorption suggesting that the anulus fibrosus may play a more important role in transferring load, and absorbing energy at these rates.